(untitled) (Fiep Bulletin - online, 2012)
The Ministry of Health Brazil has had a significant increase in the number of elderly. Aging impairs the ability of the central nervous system to perform the signal processing vestibular, visual and proprioceptive responsible for maintaining body balance. In more than half the cases the imbalance originates between 65 and 75 years approximately, and about 30% of elderly patients have the symptoms at this age. The Pilates Method is a technique that is most commonly used by physiotherapists. It is an exercise system that promotes balance between body and mind. This method, developed by Joseph Hubertus Pilates, provides well-being, health and a better quality of life. The objective of this study was to analyze the influence that the exercises of the Pilates method can provide for balance in the elderly. Was indicated by the physical therapist Pilates studio in the city of Lages-SC 7 students who have aged 60 years or more of both sexes. Applied questionnaire with closed questions and protocol for Tinetti balance assessment. The Pilates class was held on a weekly two classes. The results show that 75% of respondents have had an episode of fall. And 57% have some orthopedic pathology, systemic 29% and 14% respiratory. And 57% of participants maintained a high level of balance after the 11 Pilates classes and a 43% average rate. Therefore, the practice of Pilates offers a positive effect on balance in elderly subjects, functioning as an important tool for reducing the risk of falls are common in the aging process.